Force-responsive ordered carbonaceous frameworks synthesized from Ni-porphyrin. Issue 49 (26th May 2021) - Chida, Koki; Yoshii, Takeharu; Takahashi, Kazuma; Yamamoto, Masanori; Kanamaru, Kazuya; Ohwada, Mao; Deerattrakul, Varisara; Maruyama, Jun; Kamiya, Kazuhide; Hayasaka, Yuichiro; Inoue, Masataka; Tani, Fumito; et al.
Abstract : We have succeeded in the synthesis of a new type of ordered carbonaceous framework (OCF) with developed microporosity and a non-stacked graphene-based framework, which led to exhibition of unique flexibility. Abstract : Force-responsive ordered carbonaceous frameworks (OCFs) are synthesized for the first time. Carbonization of Ni porphyrin monomers having eight polymerizable ethynyl groups yields OCFs with atomically dispersed divalent Ni species and developed micropores. The highest specific surface area (673 m 2 g −1 ) among the OCFs has been achieved. The OCFs thus synthesized comprise non-stacked graphene sheets, affording a unique mechanical flexibility that enables force-driven reversible phase transition.